Potential Role of Antioxidant and Anti-Inflammatory Therapies to Prevent Severe SARS-Cov-2 Complications - Fratta Pasini, Anna M. (Antioxidants (Basel), 2021)
The coronavirus disease 2019 (COVID-19) pandemic is caused by a novel severe acute respiratory syndrome (SARS)-like coronavirus (SARS-CoV-2). Here, we review the molecular pathogenesis of SARS-CoV-2 and its relationship with oxidative stress (OS) and inflammation. Furthermore, we analyze the potential role of antioxidant and anti-inflammatory therapies to prevent severe complications. OS has a potential key role in the COVID-19 pathogenesis by triggering the NOD-like receptor family pyrin domain containing 3 inflammasome and nuclear factor-kB (NF-kB). While exposure to many pro-oxidants usually induces nuclear factor erythroid 2 p45-related factor2 (NRF2) activation and upregulation of antioxidant related elements expression, respiratory viral infections often inhibit NRF2 and/or activate NF-kB pathways, resulting in inflammation and oxidative injury. Hence, the use of radical scavengers like N-acetylcysteine and vitamin C, as well as of steroids and inflammasome inhibitors, has been proposed. The NRF2 pathway has been shown to be suppressed in severe SARS-CoV-2 patients. Pharmacological NRF2 inducers have been reported to inhibit SARS-CoV-2 replication, the inflammatory response, and transmembrane protease serine 2 activation, which for the entry of SARS-CoV-2 into the host cells through the angiotensin converting enzyme 2 receptor. Thus, NRF2 activation may represent a potential path out of the woods in COVID-19 pandemic.